THE INFLUENCE OF IMPLEMENTING AUTHENTIC ASSESSMENT ON STUDENT’S LEARNING ACHIEVEMENT IN THE FIQH SUBJECT AT MA NURUL JADID PAITON PROBOLINGGO - Almaknunah, Luluk (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Teachers' difficulty in evaluating learning, especially in fiqh subjects, is one of the problems in achieving learning objectives. Therefore, an assessment is needed to measure the effectiveness of the use of curriculum, strategies, and learning processes. As with the use of the 2013 curriculum, which applies a system of assessment of attitudes, knowledge and skills. This assessment is often called authentic assessment. Therefore, the purpose of this study is to determine how much influence the application of authentic assessment has on student learning achievement in fiqh subjects. This study involved 67 students of MA Nurul Jadid class XII IPA Regular 2 and XII IPA Regular 3. This research uses quantitative methods of correlative or causal associative techniques, with correlation analysis using person product moment. Data collection was obtained from the results of written tests and questionnaires. The analysis results show the correlation between variables x and y, which is 0.064 with a value of r = 0.227. These results when consulted to the interpretation column show a low correlation between x and y which is in the range of 0.20 -0, 399. so the Sig. (2-tailed) value = 0.064 which is greater than 0.05 (0.064>0.05). So it can be concluded that Ha is accepted and H0 is rejected. That is, there is an influence between the application of authentic assessment on student learning achievement but it is still low..